Relation of health-related quality of life with abnormal weight: A cross-sectional study prior to the weight reduction intervention - Abdolreza Sotoodeh Jahromi; Karamatollah Rahmanian (Journal of Family Medicine and Primary Care, 2020)
Objective: Obesity is a major health issue that is well-documented association with morbidity and mortality. The aim of this study was to investigate the associations between health-related quality of life (HRQOL) and abnormal body mass index (BMI) levels. Materials and Methods: This descriptive study assessed 134 healthy individuals with abnormal BMI aged 18–39 years, clustered into three weight categories. The Short-form (SF)-36 Questionnaire was used for measuring of HRQOL. Results: Linear-regression analyses discovered the negative correlation between BMI and the general health element of HRQL, however, a positive relation to role emotional dimension. But BMI was not associated with other six dimensions, and also with physical and mental component summary and with total health quality of life. Conclusion: BMI was an important detriment factor for the general health dimension of HRQL with regression analysis. The higher grade of abnormal BMI had a negative influence on general health and positive effect on the role emotional dimension of HRQOL.